Principles and frequency of self-adjustment of insulin dose in people with diabetes mellitus type 1 and correlation with markers of metabolic control. (June 2016) - Kramer, Guido; Kuniss, Nadine; Kloos, Christof; Lehmann, Thomas; Müller, Nicolle; Wolf, Gunter; Lorkowski, Stefan; Müller, Ulrich A.
Highlights: This is the first study dealing with principles and frequency of self-adjustment of insulin dose in people with diabetes type 1. Only half of the patients (48%) used the complex rules (factor for correction) to determine their insulin dose in case of high blood glucose levels. Personal experience/feeling is used in 44% of the people with diabetes type 1. There were no differences in HbA1c and frequency of non severe hypoglycaemia between people adjusting insulin dose by personal experience/feeling and those using adjustment rules. Abstract: Objective: Insulin dose self-adjustment (ISA) to different blood glucose levels, carbohydrate intake, exercise or illness is a core element of structured education programmes for people with diabetes mellitus type 1 (DM1). The aim of this study was to register the patients' current principles and frequency of ISA and to check the ability for correct adjustments. Research design and methods: 117 people with DM1 (mean HbA1c 7.1%, diabetes duration 24 y) were interviewed in a tertiary care centre. The number of ISA was drawn from the last 28 days of the patients' diary. The ability to find the correct insulin dose was assessed using five different calculation examples. All patients had participated in a structured education programme. Results: Mean frequency of ISA was 72.1 ± 29.4 per 28 days. ISA by adjustment rules was used in 48% (56/117) and by personal experience or feeling in 44% (52/117). Patients adjusting by feeling were older, did less ISA and had lower social status. There were no differences in HbA1c (feeling 7.2 ± 0.8 vs . rules 7.0 ± 0.9, p  = 0.403), non severe hypoglycaemia (feeling 1.7 ± 1.8 vs . rules 1.9 ± 1.9, p  = 0.132) and comprehensibility of ISA between both groups. Overall, the participants answered on average 2.8 ± 2.3 of the five calculation examples correctly. Conclusions: Although all people were trained to use a factor for correction for ISA in case of high premeal blood glucose levels, only half of the patients adjusted their insulin dosage using the complex rules from the treatment and education programme. Patients, who performed their ISA based upon feeling, did not show worse metabolic control.